A study on the effect of team composition toward organizational performance at Syarikat Air Terengganu (SATU) Sdn. Bhd. / Siti Nur Asyiqin Ibrahim - Ibrahim, Siti Nur Asyiqin (Faculty of Business Management, 2018)
This research is to discovering study the effect of team composition toward organizational performance at Syarikat Air Terengganu (SATV) Sdn. Bhd. the element of team composition are teamwork, team size and team effectiveness. 36 set of questionnaire has been distributed to the respondents in order to collect the data and all the questionnaire has been return completely 100%. This study uses the Statistical Package for Social Science (SPSS) version 21.0 to analyze the result. The descriptive analysis and Pearson correlation has been used in order to reply to the research question. All the result reveals that each element has a positive and negative effect to the organizational performance.